Contratos de franquia: origem, evolução legislativa e controvérsias - Sister, Tatiana Dratovsky (2020)
This dissertation focuses on the franchise contracts, their foundation, legal development, and relevant disputes primarily but not only in relation to termination causes. This is a contract governed by Law No. 13.966 / 2019. This is a pivotal issue, the more so in a country that currently ranks fourth among the countries with the largest number of franchises for the sale of products and services. The summary of the history of the origin and evolution of the franchising system in the United States and later in Brazil, follows to define its concept, legal nature, object, main obligations, advantages and disadvantages. It then addresses the legislative context applicable to the franchise system in Brazil. Like any long-term contract, there are countless situations that can lead to deterioration of the relationship of the parties involved. Thus, after analyzing the cases for termination of contracts in general, this piece addresses the solutions applied, whether by the Judiciary Branch or in arbitration procedure, to specific cases involving franchise agreements, notably, but not only, when the contract is terminated